Effectiveness of minimally invasive surgery using incomplete phalangeal osteotomy for symptomatic curly toe of adults with a trapezoidal phalanx: An observational study - Ramírez-Andrés, Leonor; Nieto-García, Eduardo; Nieto-González, Elena; López-Ejeda, Noemí; Ferrer-Torregrosa, Javier (Frontiers in Surgery, 2022)
Background and aims: Digital deformity in flexion, varismus (external rotation), and adduction with the toe in both supraduction and infraduction is called clinocampodactyly or curly toe. All adult patients with symptoms and diagnosed with semi-rigid/rigid curly toes underwent radiological examination to verify the presence of a trapezoidal phalanx. The degree of improvement of the dysmetric phalanx after incomplete phalangeal osteotomy (IPO) was assessed using minimally invasive surgery and the American Orthopedic Foot and Ankle Society (AOFAS) scale score. Methods Between May 2020 and June 2021, 30 patients diagnosed with curly toes underwent unicortical osteotomy of the affected phalanx. The convergence angle was measured and the AOFAS scale scores were compared. Results Thirty-three toes underwent surgery. The average reduction of the convergence angle was 9 degrees. The average improvement in the AOFAS scale score was 53 points at 6 months and reached almost 90 points (89.9 ± 6.1 points). Conclusions IPO performed with minimally invasive surgery of the trapezoidal phalanges of curly toes of adults can improve alignment and AOFAS scale scores.